2006
DOI: 10.1158/0008-5472.can-06-1507
|View full text |Cite
|
Sign up to set email alerts
|

The CXCR5 Chemokine Receptor Is Expressed by Carcinoma Cells and Promotes Growth of Colon Carcinoma in the Liver

Abstract: The chemokine receptor CXCR5 is expressed by B cells and certain T cells and controls their migration into and within lymph nodes. Its ligand BCA-1/CXCL13 is present in lymph nodes and spleen and also in the liver. Surprisingly, we detected CXCR5 in several mouse and human carcinoma cell lines. CXCR5 was particularly prominent in pancreatic carcinoma cell lines and was also detected by immunohistochemistry in 7 of 18 human pancreatic carcinoma tissues. Expression in CT26 colon carcinoma was low in vitro, upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 30 publications
7
69
0
1
Order By: Relevance
“…In one report, immunohistochemistry revealed CXCR5 expression in a significant proportion of human colon carcinoma specimens (Gunther et al, 2005), whereas another group demonstrated cytoplasmatic expression in pancreatic cancer cells and cell lines (Meijer et al, 2006). We show here for the first time that the ligand for CXCR5, CXCL13, is the most significantly overexpressed chemokine in breast cancer, supporting the idea of a role of CXCL13/CXCR5 interactions in promoting initiation and/or progression of this tumour type and, possibly, other human cancers.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In one report, immunohistochemistry revealed CXCR5 expression in a significant proportion of human colon carcinoma specimens (Gunther et al, 2005), whereas another group demonstrated cytoplasmatic expression in pancreatic cancer cells and cell lines (Meijer et al, 2006). We show here for the first time that the ligand for CXCR5, CXCL13, is the most significantly overexpressed chemokine in breast cancer, supporting the idea of a role of CXCL13/CXCR5 interactions in promoting initiation and/or progression of this tumour type and, possibly, other human cancers.…”
Section: Discussionsupporting
confidence: 67%
“…Importantly, a concentration gradient-and time-dependent downregulation would also explain our observation of a strong correlation between CXCL13 expression and the presence of its receptor within breast cancer tissues despite the lack of CXCR5 overexpression in the same tissues. In addition, the hypothesis that an externalisation of receptor CXCR5 is restricted to certain phases of cancer development in vivo is also supported by the findings of Meijer et al (2006) who did not detect CXCR5 expression on a variety of tumour cell lines cultured in vitro but who found this chemokine receptor to be expressed on the surface of the same cells several days after injection into mice.…”
Section: Discussionmentioning
confidence: 82%
“…Activation of bone-resorbing osteoclasts at the tumor-bone interface facilitates the osteolytic process and bone invasion of cancer cells (14). Recent studies indicated CXCR5 chemokine receptor expression by colon carcinoma cells and potential role in tumor growth (19). Therefore, our findings that CXCL13 stimulates RANKL expression in OSCC cells implicates a potential role in osteolysis associated with OSCC and tumor cell invasion of bone.…”
Section: Discussionsupporting
confidence: 50%
“…For instance, CXCR1, CXCR2 and CXCR3 in malignant melanoma [96,97]; CXCR3 in B-cell chronic lymphocytic leukemia cells [98]; CXCR5 in liver metastasis of colorectal carcinoma [99]. The CX3CR1 receptor is implicated in the perineural invasion frequently occurring in pancreatic adenocarcinoma [76] and in metastasis to bone of prostatic tumors [100].…”
Section: Tumor Cell Invasion and Migration To Distant Organsmentioning
confidence: 99%